2017
DOI: 10.1111/scs.12555
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of factors associated with older persons’ perceptions of the benefits of and satisfaction with a preventive home visit service

Abstract: Annual, comprehensive PHVs to a general older population may support older persons' health and independence. Low response rate restricts the possibility to generalise the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
(89 reference statements)
0
10
1
Order By: Relevance
“…Toien et al (2018) assessed the perceived benefits and opinions of preventive health visits (PHVs) to older people in Norway. These annual visits were designed to address multiple dimensions of access; as they were delivered free of charge (affordability) and involved assessing older people's health status and life situation, then providing personalised support (acceptability) including information and referrals to services (awareness).…”
Section: Resultsmentioning
confidence: 99%
“…Toien et al (2018) assessed the perceived benefits and opinions of preventive health visits (PHVs) to older people in Norway. These annual visits were designed to address multiple dimensions of access; as they were delivered free of charge (affordability) and involved assessing older people's health status and life situation, then providing personalised support (acceptability) including information and referrals to services (awareness).…”
Section: Resultsmentioning
confidence: 99%
“…According to Tøien et al. (2017), an annual, comprehensive intervention should be realised to support health and independence of older people. Finally, based on the results, a basic consultation with several consecutive home visits can be recommended, which should be continued in the following years as needed, or example once a quarter or every six months.…”
Section: Discussionmentioning
confidence: 99%
“…(2016), the acceptance seems to be rather low so far. It is therefore “… less a question of WHETHER, but of HOW in terms of design, settlement and unfolding” (Schulz‐Nieswandt et al., 2018, p. 8), and the experiences of the persons concerned have to be collected to enhance the effectiveness (Tøien et al., 2017). For this reason, evaluations of PHVs should focus on the individual perspective of the older people.…”
Section: Introductionmentioning
confidence: 99%
“…Participants felt that the community nurse and physical therapist kept an extra eye on them post-discharge, which contributed to medication adherence and a sense of security to perform CR exercises. Previous studies also reported that patients felt safe when preventive home visits were delivered [ 29 , 30 ]. However, participants had some difficulties to mention the specific role of the community care nurse which was primary to recognize health deterioration early.…”
Section: Discussionmentioning
confidence: 99%